Pemberian Diskon Pada Aplikasi T-Money Bank Bengkulu Perspektif Hukum Islam - Sitorus, Iwan Ramadhan; Mursalin, Supardi; Ratri, Nofi Nurahma (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
This study aims to determine the provision of discounts on transactions using the Bengkulu Bank T-Money Application in Islamic Law review. This type of research used in this research is qualitative, using descriptive methods. The results of this study found that the giving of discounts on the T-Money Bank Bengkulu application was given in the form of cashback during launching and events that were planned to be held periodically. The discount given at launch came from Bank Bengkulu and Telkom, while the discount for the event was fully borne by Bank Bengkulu. Giving discounts on the T-Money application of Bank Bengkulu with an Islamic legal perspective is that the contract in the implementation of T-Money is the Wadiahyad Dhamanah contract and giving discounts in the form of cashback by sharia provisions because, in the Wadiahyad Dhamanah contract, fund depositors are allowed to give bonuses to fund owners. Until now there has been no argument that prohibits the use of T-Money and in its use, there are problems for mankind.